2015
DOI: 10.3174/ajnr.a4576
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Cerebral Embolism and Carotid Intraplaque Hemorrhage during Protected Carotid Artery Stenting

Abstract: BACKGROUND AND PURPOSE: Carotid artery stent placement in patients with intraplaque hemorrhage remains controversial because of the incidence of cerebral embolism after the procedure. The purpose of this study is to determine if intraplaque hemorrhage is a significant risk factor for cerebral embolism during carotid artery stent placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…To the best of our knowledge, disruption of carotid plaques triggers the formation of thromboembolus and subsequent ischemic stroke. In addition, some previous studies documented that no association can be found between the presence of IPH and ischemic stroke [23]. Our findings suggest that quantification of the size of IPH is warranted in patients with carotid plaques in stratification of stroke risk beyond the mere presence of IPH.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…To the best of our knowledge, disruption of carotid plaques triggers the formation of thromboembolus and subsequent ischemic stroke. In addition, some previous studies documented that no association can be found between the presence of IPH and ischemic stroke [23]. Our findings suggest that quantification of the size of IPH is warranted in patients with carotid plaques in stratification of stroke risk beyond the mere presence of IPH.…”
Section: Discussionmentioning
confidence: 55%
“…Third, carotid vessel wall imaging of our study was performed with 2D multicontrast CMR imaging protocol with limited longitudinal coverage which may not capture the atherosclerotic plaque in more proximal or distal segments of extracranial carotid arteries. Wang et al [27] proposed a simultaneous noncontrast angiography and intraplaque hemorrhage sequence with large longitudinal coverage [23] which could be used to evaluate carotid IPH in future studies.…”
Section: Discussionmentioning
confidence: 99%
“… 3 5) Recent quantitative color-coded T1-weighted MR plaque imaging for preoperative plaque diagnosis can accurately distinguish lipid core and intraplaque hemorrhages (IPHs) 5) ; however, high-resolution MRI is not always an option for patients before revascularization. 6) An additional imaging modality that can accurately identify the lipid components of carotid plaque at high risk for embolic complications during CAS would be therefore required.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study from our group (20), we reported that IPH is not a significant risk factor for cerebral embolism during CAS in patients with severe carotid artery stenosis. However, to the best of our knowledge, the relationship between unstable plaque on carotid HR-MRI and the safety of CAS have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a group studied the relationship between the presence of unstable plaque such as IPH on carotid HR-MRI and the development of ischemic stroke in previously asymptomatic and symptomatic patients (18)(19)(20)(21). In particular, IPH is associated with plaque progression and consequently induces luminal narrowing (22,23).…”
Section: Introductionmentioning
confidence: 99%